$\displaystyle 2[\log_{2}(x+5)]^2 + \log_{2}(x-5)\log_{2}(x+5) = [\log_{4}(x^2-10+25)]^2$

I was able to simplify until it became

$\displaystyle 2[\log_{2}(x+5)]^2 + \log_{2}(x-5)\log_{2}(x+5) = [\frac{\log_{2}(x-5)^2}{2}]^2$

Then I said: Let $\displaystyle a= \log_{2}(x+5)$ and let $\displaystyle b= \log_{2}(x-5)$

so it becomes $\displaystyle 2a^2 + ab = (\frac{2b}{2})^2$

I don't know where to go from there. I'm trying to get a system of equation, but I can't seem to get another equation.

Thanks in advance.